2009
DOI: 10.1073/pnas.0901641106
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell membrane tension by myosin-I

Abstract: All cell functions that involve membrane deformation or a change in cell shape (e.g., endocytosis, exocytosis, cell motility, and cytokinesis) are regulated by membrane tension. While molecular contacts between the plasma membrane and the underlying actin cytoskeleton are known to make significant contributions to membrane tension, little is known about the molecules that mediate these interactions. We used an optical trap to directly probe the molecular determinants of membrane tension in isolated organelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
138
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 51 publications
11
138
0
Order By: Relevance
“…Membrane tension is the loading force that growing actin filaments fight in order to protrude the membrane [30]. It was previously demonstrated that inhibiting the function of class I myosins function decreased the membrane tension in fibroblasts [42] and that down-regulation of Myo1g expression in T cells gives the same effect. According to this, it has also been observed that the decrease in membrane tension correlates with an increased protrusion generation in fibroblasts [43] and the uniform peripheral expansion of the leading edge and loss of polarity of migrating neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane tension is the loading force that growing actin filaments fight in order to protrude the membrane [30]. It was previously demonstrated that inhibiting the function of class I myosins function decreased the membrane tension in fibroblasts [42] and that down-regulation of Myo1g expression in T cells gives the same effect. According to this, it has also been observed that the decrease in membrane tension correlates with an increased protrusion generation in fibroblasts [43] and the uniform peripheral expansion of the leading edge and loss of polarity of migrating neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of an EGFP-tagged Myo1-TH1 in cell lines causes a dominant negative phenotype (28,29), which disrupts the targeting of endogenous class I myosins and confers cellular characteristics similar to those observed in Myo1a and Myo1e KO mice (12,30). By transfecting an EGFP-tagged Myo1c-TH1 construct, we expected to block the function of endogenous Myo1c in the A20 mature mouse B cell line.…”
Section: Extent Of B Cell Spreading Is Dependent Of Myo1c Functionmentioning
confidence: 99%
“…The myosin-1 tail contains a tail homology 1 (TH1) domain that interacts with acidic phospholipids and, in some cases, also contains a glycine-and proline-rich TH2 domain that binds filamentous actin and an Src homology 3 domain that forms complexes with proteins that stimulate actin filament assembly (4 -10). Myosin-1 is able to cross-link the plasma membrane to the underlying actin cytoskeleton and plays a direct role in the control of cortical and membrane tension (11,12). These motor proteins can also drive vesicle trafficking, pseudopod retraction, and the uptake of particles and fluids by phagocytosis and micropinocytosis (13-16).…”
mentioning
confidence: 99%